Tracking Control of Electronic Cam Trajectory based on the Electromagnetic Linear Actuator - Wang Cai; Chang Siqin (Jixie chuandong)
An electronic cam based on the electromagnetic linear actuator is proposed,by tracking the given trajectory to realize the required linear motion law and substitute the traditional cam mechanism. The electric cam is controlled by the iterative learning control algorithm to realize the track of the target trajectory. Moreover,the adoption of both iterative learning control algorithm and fuzzy sliding mode control can effectively improve the convergence speed and robustness of the electric cam. The fuzzy sliding mode iterative control is inputting the error function in sliding mode controller,which takes the function of a sliding mode control as the input of fuzzy control and takes the fuzzy control output as the control increment of iterative learning control. The simulation and the experiment shows that electronic cam based on the electromagnetic linear actuator can effectively substitute traditional cam mechanism,and the fuzzy sliding mode iterative control algorithm can satisfy the requirements of the precision of trajectory tracking,response speed,convergence speed and robustness of electronic cam.